2009
DOI: 10.1042/ba20090219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of model morpholine derivatives with biological activities by laccase‐catalysed reactions

Abstract: The efficient enzyme-catalysed reaction of morpholines as model structures for bioactive compounds with para-dihydroxylated aromatic systems was carried out using the oxidoreductase laccase and atmospheric oxygen to produce eight novel morpholine-substituted aromatics. The laccase of Myceliophthora thermophila was used for cross-linking morpholines containing primary or secondary amino groups with para-dihydroxylated laccase substrates. We demonstrate that not only primary amino groups, but also secondary amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…For reactions of para-dihydroxylated aromatic substances and amino compounds yields of 20-80% are achievable [12] and for optimized reactions a yield of 96% is possible [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For reactions of para-dihydroxylated aromatic substances and amino compounds yields of 20-80% are achievable [12] and for optimized reactions a yield of 96% is possible [6].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this hydroxylated product can undergo a coupling reaction with 3c or 3d as described for the heteromolecular reaction of 2,5-dihydroxy-N-(2-hydroxyethyl)-benzamide and morpholine [12].…”
Section: Second Reaction Typementioning
confidence: 99%
See 1 more Smart Citation
“…C NMR chemical shift for C-2 of 2-alkylamino-1,4-naphthoquinones from primary amines ranged from 144.8 ppm to 149.0 ppm, 10,12,17,[21][22][23] and more upfield than those of secondary amines (ranging from 150.6 ppm to 154.0 ppm). 10,[23][24][25][26] From the data in table 3, it can be observed that the C-2 chemical shift of dialkylamino derivatives ranges from 150.0 ppm to 154.1 ppm (5b-e,5j, 6b-h, 6j 28 both using the same methodology, are in reality easily understood if we rationalize they are actually alkyl-and dialkylammonium salts of lapachol and thus are not the result of the claimed substitution reactions. The absence of HMBC correlation between the carbon chain of amine with C-2 further compromises the conclusions put forward by these authors.…”
Section: Scheme 3 Partial Hydrogenation Of 2-methoxy-lapachol (1a) Smentioning
confidence: 99%
“…1). The morpholine scaffold is very versatile and was featured in a number of biologically and pharmacologically active products such as vasorelaxant, 17) anticancer, 18) antioxidant, 19,20) analgesic, 21) antimicrobial 22,23) and antiparasitic agents. 24) Mannich bases with morpholinomethyl of synthetic flavonoids exhibited good effects during global ischemia and perfusion in rat brain.…”
mentioning
confidence: 99%